The Influence of Electronic Service Quality and Service Convenience on User Loyalty Through User Satisfaction in The CITA Sampoerna Application in Tanjung Morawa District - Rospita Simamora; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (Indonesian Journal Publisher, 2026)
The development of digital technology has driven changes in business activities, particularly through the use of e-commerce–based applications that increasingly facilitate business actors in carrying out their operations. However, in the CITA Sampoerna application, there are still challenges in creating sustainable user satisfaction, which may ultimately affect user loyalty. This condition indicates that the service experience perceived by users, both in terms of system quality and ease of service access, is an important aspect that needs to be considered in order to maintain the continued use of the application amid the abundance of similar service alternatives. This study aims to examine and analyze the effect of electronic service quality and service convenience on user loyalty through user satisfaction in the CITA Sampoerna application in Tanjung Morawa District. This research employs a quantitative approach with an associative research type. The population of this study consists of 250 users (partners) of the CITA Sampoerna application in Tanjung Morawa District, with a sample of 146 respondents determined based on the Isaac & Michael table. The sampling technique used is probability sampling with a simple random sampling method. The data used include primary and secondary data obtained through questionnaires and documentation studies. The data analysis technique used is Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine the structural relationships among variables. The results show that electronic service quality and service convenience have a direct positive and significant effect on user loyalty and user satisfaction among users of the CITA Sampoerna application. Furthermore, indirect testing results also indicate that electronic service quality and service convenience have a positive and significant effect on user loyalty through user satisfaction among users of the CITA Sampoerna application in Tanjung Morawa District.